2007
DOI: 10.4049/jimmunol.179.1.691
|View full text |Cite
|
Sign up to set email alerts
|

Inhibited Aortic Aneurysm Formation in BLT1-Deficient Mice

Abstract: Leukotriene B4 is a proinflammatory lipid mediator generated by the enzymes 5-lipoxygenase and leukotriene A4 hydrolase. Leukotriene B4 signals primarily through its high-affinity G protein-coupled receptor, BLT1, which is highly expressed on specific leukocyte subsets. Recent genetic studies in humans as well as knockout studies in mice have implicated the leukotriene synthesis pathway in several vascular pathologies. In this study, we tested the hypothesis that BLT1 is necessary for abdominal aortic aneurysm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 35 publications
(50 reference statements)
0
66
0
Order By: Relevance
“…Apolipoprotein E and BLT 1 R double knockout mice display smaller lesions compared with their apoE(Ϫ/Ϫ) littermates Heller et al, 2005;Bä ck, 2008b). The latter double knockout mice are also protected from abdominal aortic aneurysm development induced by angiotensin II infusion (Ahluwalia et al, 2007).…”
Section: E Blt Receptor Functional Analysis Through Altered Gene Expmentioning
confidence: 90%
See 1 more Smart Citation
“…Apolipoprotein E and BLT 1 R double knockout mice display smaller lesions compared with their apoE(Ϫ/Ϫ) littermates Heller et al, 2005;Bä ck, 2008b). The latter double knockout mice are also protected from abdominal aortic aneurysm development induced by angiotensin II infusion (Ahluwalia et al, 2007).…”
Section: E Blt Receptor Functional Analysis Through Altered Gene Expmentioning
confidence: 90%
“…The importance of BLT 1 R signaling has also received support from animal studies. Either genetic or pharmacological targeting of BLT 1 R signaling reduces the incidence of experimental abdominal aortic aneurysms induced by angiotensin infusion in apoE knockout mice (Ahluwalia et al, 2007;Kristo et al, 2010).…”
Section: F Potential Therapeutic Applicationsmentioning
confidence: 99%
“…The results of several recent studies suggested the importance of BLT1 in atherosclerosis. BLT1 deficiency resulted in reduced atherogenesis in an apoE-deficient background (16), and this effect was explained by reduced level of production of monocyte chemoattractant protein-1 (MCP-1) in BLT1-deficient macrophages (47). Future studies investigating the possible role of LTB 4 -BLT1 signaling, especially Rac activation, in MCP-1 production in macrophages would be of particular interest.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of LTB4 to affect such a wide range of cell types indicates that LTB4 may function broadly in the regulation of innate and adaptive immune responses. LTB4 is essential in host defense against bacterial infection (40), and is linked to many inflammatory disorders, including arthritis (41)(42)(43), atherogenesis (44), and aortic aneurysm formation (45). In animal models and in patients with asthma, the levels of LTB4 have been reported to be elevated in the airways and to correlate with asthma severity (15,16,38,46).…”
Section: Discussionmentioning
confidence: 99%